The Students’ Taking an Interest in Social Networks: Psychological Features - Mitlosh, Antonina (Psychological Prospects Journal, 2014)
The paper analyzes the results of the theoretical and empirical study of psychological characteristics of students showing interest to social networks. The author argues the relevance of the chosen topic, because it wasn’t studied comprehensively in the applied and theoretical aspects. The paper draws attention to the fact that Ukraine has entered the top five countries where Internet users visit social networks most active. The study provides the data of the standardized interview, which was conducted with students of the first course at the Lesya Ukrainka Eastern European National University, in order to form groups of samples investigated. The next stage of the study was to clarify the characteristics of value-motivational sphere of the subjects who use online social networks. The comparison of the results with the application of V. Milman test shows that people, who use social networks very often, are mostly business oriented. The author also argues that most users of Facebook social network showed business orientation in their motivational structure. Among the main motives in the motivational sphere of social networks’ users are: motives of affiliation and cooperation (the desire to help others to increase in this way their authority, achieving recognition by others of their own competence and skill), self-determination, self-fulfillment (as a way of expression and development of their intellectual and creative potential), and business (focused on specific business results), communicative, cognitive (new knowledge) motives.